2022
DOI: 10.1001/jamanetworkopen.2022.45909
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use and Incidence of Adverse Oral Health Outcomes Among US Adults in the Population Assessment of Tobacco and Health Study

Abstract: ImportanceEvolving tobacco use patterns, including increasing electronic nicotine delivery systems (ENDS) use, warrant re-examination of the associations between tobacco use and oral health.ObjectiveTo examine associations between tobacco product use and incidence of adverse oral health outcomes.Design, Setting, and ParticipantsThis cohort study used nationally representative data from wave (W) 1 to W5 (2013-2019) of the Population Assessment of Tobacco and Health Study. Recruitment used a stratified address-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…14 Over time, tobacco degrades the gums and can trigger tooth loss. 15 Fortunately, effective medications are available for both alcohol use disorder and tobacco use disorder and should be encouraged as early as possible to optimize patient outcomes and life expectancy.…”
Section: Emerging Perspectives In Addiction Psychiatrymentioning
confidence: 99%
“…14 Over time, tobacco degrades the gums and can trigger tooth loss. 15 Fortunately, effective medications are available for both alcohol use disorder and tobacco use disorder and should be encouraged as early as possible to optimize patient outcomes and life expectancy.…”
Section: Emerging Perspectives In Addiction Psychiatrymentioning
confidence: 99%
“…Moreover, oral and dental diseases share common risk factors with cardiovascular diseases, which are multifactorial in nature, influenced by lifestyle choices, diet, physical activity, tobacco use, and more [ 10 ]. Studies have shown that oral microbiota, in addition to these risk factors, can contribute to the incidence of cardiovascular diseases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%